Determinación de la ropa de trabajo para el despachador de una empresa de productos cárnicos con exposición a estrés por frío en la empresa INCUBANDINA-Laso - Lara Padilla, Paola Grimaneza (2022)
The present research was conducted at the enterprise INCUBANDINA S.A in Laso. Hence, the work clothes for the meat dispatcher who is exposed to cold stress in the storage chambers were determined. The research design is non-experimental cross-sectional, type quantitative and qualitative. The storage area is operated by a dispatcher so that our population and sample is a worker. There are two storage chambers in which 10,000 to 12,000 chickens are deposited daily. In such a manner, a study of the dispatcher's job was conducted by means of the observation level of the 2A method contingent on the ISO 8996 standard. Not only that, through the tables of the NTP 323, it was determined that the energy consumption of the dispatcher's basal metabolism is 45,634 w/m^2, body position metabolism is 25 w/m^2, work type metabolism is 65 w/m^2, and displacement metabolism is 11 w/m^2 having an average energy consumption is146,634 w/m^2. Hence, the thermo-hygrometric conditions were measured based on the 27243 normative. In addition, the WBGT meter was utilized. A homogeneous measurement was made at the height of the dispatcher's chest in which the following results were obtained: On the one hand, there is an Air Temperature of 3.6°C, a Globe Temperature of 3.7°C, and a Relative Humidity of 56.4% in storage chamber 1, On the other hand, there is an Air Temperature of 0°C, a Globe Temperature of 0°C, and a Relative humidity of 47% in the storage chamber 2. Eventually, it was established through ISO 11079 and NTP 462, in order for the dispatcher to have an adequate thermal resistance, in the 8 hours of work in storage chambers 1 and 2, it is imperative to wear the following work clothes: long underpants that have thermal resistance of 0.10 chlo, long-sleeved shirt of 0.12 chlo, flannel pants of 0.28 chlo, horrible pullover of 0.35 chlo, work coverall of 0.90 chlo, horrible and long socks of 0.10 chlo, 0.10 chlo boots, 0.30 chlo cap and 0.05 chlo gloves, with these garments the dispatcher has a thermal resistance of 2.33 chlo and cannot contract cold stress.